Prediction of performance in the half-marathon from lactate-velocity relationship in a field test - Santos, P. J. (Medicine & Science in Sports & Exercise, 1998)
This study investigated the validity of a field test for predicting half-marathon running time. Long-distance runners (N = 18) performed a total of 33 half-marathons and an equal amount of incremental field tests (4 x 2,000 m) to establish the relationship between running speed and blood lactate levels. Speeds used in the field test ranged from 4.2 to 5.8 m/s with increments of 0.4 m/s in each step. Following each loading level blood samples were taken from the ear lobe and analyzed using a YSI-1500 Sport. Statistical analyses included correlations and a simple linear regression model. Level of significance was set at 5%. Test speeds corresponding to lactate concentrations between 3.0 and 5.5 mM showed a high correlation with half-marathon speed. However, even higher correlations were found at lactate levels of 4.5, 5.0, and 5.5 mM running speeds. Despite these strong correlations in practical terms the data did not predict well. 70% of the athletes' final competition times fell outside the 5% level of prediction based on the lactates of 4.5 - 5.5 mM. Implication. Predicting long-distance running times on the basis of lactate velocity relationships does not yield practical results.